Sand Minerals on the Soils of South Kheri Forests' Uttar Pradesh - Banerjee, S. P.; Raina, A. K.; Mathur, K. C. (Indian Forester, 1988)
Mineralogical study of the fine sand fraction of ten typical soils of 'South Kheri forests of Uttar Pradesh brings out that quartz is the preponderant detrital mineral in all these alluvial soils followed by mica which is higher in lower depths' especially the muscovite type. The heavy minerals which are present in small quantities' include mainly chlorite' iron-ores and tourmaline' and in very small quantities zircon' sphene' staurolite' apatite' garnet' bornblende' kyanite and epidote. Petrographic examination revealed that excepting quartz' which is in abundance throughout the depth of the pedons' no other mineral' light or heavy' shows any definite trend of distribution along the depths of the pedons. No definite relationship appears to exist between the nature of these skeletal minerals and growth' development and distribution of the vegetation of the area.